Just Transition and Place-Based Policy in Coal-Dependent Areas - Topaloglou, Lefteris (Business Management and Strategy, 2021)
Recently, the interrelated concepts of the place-based approach, spatial justice, and just transition appear not only in scientific dialogue but also in developing policies that seek to address spatial inequalities. This article attempts to discuss the European, national, and local just transition policies and to assess the extent to which these policies are in line with the place-based model, as reflected in the Barca report (2009). The study reference area at the regional level is Western Macedonia, for which the transition towards an alternative, sustainable, and just path stands a very challenging policy exercise. The empirical section involved questionnaires with local specialists and professionals who hold profound knowledge and experience of the area. The results of the analysis revealed that just transition policies designed only at a European level demonstrate a high-level degree of relationship with the place-based model. The exact opposite seems to prevail at the level of national and regional policies.